The Relations Between Breast Cancer and Hormonal Contraception Acceptor At RSUP Dr. Mohammad Hoesin Palembang in 2021 - Nur Nabila Sabrina; Heriyadi Manan; Hadrians Kesuma Putra (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Introduction. Breast cancer is a non-communicable disease that has become a health problem in the world. One of the risk factors for breast cancer is hormonal factors that can be obtained from the use of hormonal contraception. This study describes the relationship between the incidence of breast cancer and the use of hormonal contraception at RSUP Dr. Mohammad Hoesin Palembang in 2021. Method. This is an observational analytic study with a case-control design. The data used are secondary data and primary data. The sample are women with breast cancer and benign breast tumors at RSUP Dr. Mohammad Hoesin Palembang in 2021who met the inclusion criteria. Results. There was a significant relationship between the use of hormonal contraceptives (p = 0.003), duration of the use of hormonal contraceptives>5 years (p = 0.004), the type of injectable hormonal contraceptive (p = 0.001), the type of hormonal pills (p = 0.018) and a family history (p = 0.001). Meanwhile, there was no significant relationship between the type of hormonal contraceptive implant (p = 0.724), parity (p = 1.000), and age at menarche (p = 0.129),with the incidence of breast cancer. Conclusion. There is a significant relationship between the use of hormonal contraception, duration of use of hormonal contraception >5 years, type of injectable hormonal contraceptive use, type of use of hormonal contraceptive pills, and family history of breast cancer with breast cancer incidence.